2011
DOI: 10.1371/journal.pone.0017371
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Safety and Effectiveness of Chlorproguanil-Dapsone and Lumefantrine-Artemether for Uncomplicated Malaria in Children in The Gambia

Abstract: BackgroundChlorproguanil-dapsone (Lapdap), developed as a low-cost antimalarial, was withdrawn in 2008 after concerns about safety in G6PD deficient patients. This trial was conducted in 2004 to evaluate the safety and effectiveness of CD and comparison with artemether-lumefantrine (AL) under conditions of routine use in G6PD normal and G6PD deficient patients with uncomplicated malaria in The Gambia. We also examined the effects of a common genetic variant that affects chlorproguanil metabolism on risk of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…Out of the 1,813 potential articles, 16 fulfilled the inclusion criteria ( Figure 1) [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and comprised a total of 9,247 patients. Of these, two studies included two different interventions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the 1,813 potential articles, 16 fulfilled the inclusion criteria ( Figure 1) [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and comprised a total of 9,247 patients. Of these, two studies included two different interventions.…”
Section: Resultsmentioning
confidence: 99%
“…18,22 Studies were published from 1998 to 2011. Ten studies (62.5%) were undertaken in Africa [20][21][22][23][24][25][26]29,31,32 and the remainder were set in Asia. [17][18][19]27,28,30 All the studies were based in the public healthcare sectors (12 in a hospital 17,19 -22,24 -31 and 4 in a community setting) 18,23,25,32 but one study also included a group from the private sector.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mutation in The Gambia had already been reported at surprisingly low frequency level (less than 2%) in 2004 [7]. The real frequency of this mutation in Gambian males was subsequently confirmed to be 2-3% [5,8], not 5.9% as reported by Ruwende et al The reason why they found such an inflated frequency is unknown. 3.…”
mentioning
confidence: 83%
“…For example, patients may not understand how to correctly take the medication, 45,56-60 they may forget to take their pills, 18,56,58,59 they may be saving some pills for a future malaria episode, 45,56 or they may stop taking the medication once they feel better. 61,62 In our study, we found no relationship between literacy or education and adherence, and we also found that 91% of patients took the first two doses of AL with the correct number of pills at approximately the correct time (data not shown).…”
Section: Discussionmentioning
confidence: 99%